Tracheostomy In ICU: An Insight into the Present Concepts - Muralidhar K. (Indian Journal of Anaesthesia, 2008)
Tracheostomy is a commonly performed surgical procedure in the intensive care units. Indications for tracheostomy are mainly four-fold namely airway obstruction, aspiration of secretions, airway protection from aspiration and provision of mechani-cal ventilation. Anaesthesia technique used for tracheostomy is varied and is dictated by the general condition of the patient. Percutaneous tracheostomy is an alternative to the surgical approach that can be done at the bedside and has several advan-tages. Though a simple procedure, tracheostomy can be associated with a number of life-threatening complications like hypoxia, cardiac arrest, injury to structures immediately adjacent to the trachea, pneumothoax and haemothorax.